Pengaruh Pengetahuan pajak, sanksi pajak terhadap kepatuhan pajak pada UMKM kota Medan - Hantono Hantono; Riko Fridolend Sianturi (Owner : Riset dan Jurnal Akuntansi, 2022)
This research aims to look at the influence of Tax Knowledge, Tax Actionand Tax Compliance. Data collection techniques by disseminating questionnaires, while the data analyst method used is inferenceal statistics,(inductive statistics or probability statistics),is a statistical technique used to analyze sample data and the results are applied topopulations (Sugiyono in Kalnadi 2013). In accordance with the hypothesis that has been formulated, then in this study the analysis of inferential statistical data is measured using SmartPLS software (PartialLeast Square) ranging from model measurements (outermodels), the results of the study obtained a calculated value for Tax Knowledge (X1)is smaller and sig t value for Tax Knowledge (X 1) 0.124 is greater than alpha (0.05). Based on the results obtained then receive H0 and reject H1 for Tax Knowledge (X1). Thus, partially Tax Knowledge (X1) has no positive and insignificant effect on Tax Compliance (Y), indicating Tax Knowledge (X1)does not have a positive impact in improving Tax Compliance (Y). The results ofthe study obtained nilai tcalculated for Tax Sanctions (X2) of 2,759 greater than sig t value for Tax Sanctions (X2) of 0.007 smaller than alpha (0.05). Based on the results obtained, reject H0 and receive H1. Thus partially Tax Sanctions (X2)have a positive and significant effect on Tax Compliance (Y), meaning tax sanctions (X2)have a real impact in improving tax compliance (Y).